Shoulder Arthroplasty Options for Glenohumeral Osteoarthritis in Young and Active Patients (<60 Years Old): A Systematic Review. (March 2022) - Fonte, Hélder; Amorim-Barbosa, Tiago; Diniz, Sara; Barros, Luís; Ramos, Joaquim; Claro, Rui
Aim: This study aims to describe the shoulder arthroplasty options for young and active patients (<60 years old) with glenohumeral osteoarthritis. Methods: A systematic review of the literature was conducted by searching on Pubmed database. Studies that reported outcomes of patients with glenohumeral arthritis, younger than 60 years, that underwent shoulder arthroplasty [(Hemiarthroplasty (HA), Hemiarthroplasty with biological resurfacing (HABR), Total shoulder arthroplasty (TSA), Reversed total shoulder arthroplasty (RSA)] were included. Data include patient characteristics, surgical technique, range of motion, pain relief, outcome scores, functional improvement, complications, need for and time to revision. Results: A total of 1591 shoulders met the inclusion criteria. Shoulder arthroplasty provided improvements in terms of ROM on the 3 plains, forward flexion (FF), abduction (Abd) and external rotation (ER), in different proportions for each type of implant. Patients submitted to RSA had lower preoperative FF (p = 0.011), and the highest improvement (Δ) in Abd, but the worst in terms of ER (vsTSA, p = 0.05). HA had better ER postoperative values (vsRSA p = 0.049). Pain scores improved in all groups but no difference between them (p = 0.642). TSA and RSA groups had the best CS Δ (p = 0.012). HA group had higher complication rates (21.7%), RSA (19.4%, p = 0.034) and TSA (19.4%, p = 0.629) groups the lowest, and HABR had the highest rate of revisions (34.5%). Conclusions: HA had the highest rate of complications and HABR unacceptable rates of revision. These implants have been replaced by modern TSAs, with RSA reserved for complex cases. Surgeons should be aware of the common pitfalls of each option.